The Influence of Social, Economic, and Environmental Factors on Health Quality in ASEAN - Muryani Muryani; Fairidita Annisa Indra (Global Strategis, 2019)
There is a serious problem in term of health over the past 70 years in developing countries, one of them is the quality of life expectancy. Even it has continued to increase but still there is a gap between developed and developing countries. The gap in life expectancy is assumed to be rooted in the differences in socio-economic conditions of different social groups. Health matter, especially in the ASEAN region, is an important issue that must be addressed. Therefore, this research has an objective to explore the influence of social, economic and environmental factors on health quality in ASEAN. The variables in this research are the impacts of population, urbanization, food production, GDP, health spending, and CO2 emissions on health in 9 ASEAN countries in the period from 2001-2015. The analysis method is a panel of regression data. The findings of the research are that all the independent variables have a significant effect on Health quality in ASEAN.